Pengaruh Penambahan Tepung Rumput Laut (Eucheuma sp.) Terhadap Mutu dan Karakteristik Amplang Ikan Tongkol (Euthynnus affinis) - Weni Kurnia Sari; N Ira Sari; Tjipto Leksono (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Seaweed flour is a potential source of dietary fiber expected to improve the quality of fishery products. The purpose of this study was to determine the effect of addition of seaweed flour (Eucheuma sp.) on the quality and characteristics of tuna fish amplang. The research method was using a non-factorial completely randomized design (CRD) consisting of five treatments of varied amount of seaweed flour added (0, 0.5%, 1%, 1.5%, and 2% from the total dough weight). The variables to assess the quality were the organoleptic quality and characteristics (appearance, aroma, taste and texture), swelling degree, and proximate content. The results showed that the addition of seaweed flour can improve the proximate composition of fish amplang, especially the increase in crude fiber content. The addition of seaweed flour has an optimum concentration point of 1% to produce the best tuna fish amplang with the characteristic of bright colors, clean, smooth surface, not cracked, savory taste and a crunchy and dense texture. The score of the appearance was 8.3; aroma was 7.7, taste 8.2, texture 8.5, and the swelling degree was 384%. The best product was containing water 1.14%, ash 3.82%, protein 39.59%, fat 12.92%, and fiber 5.79%. The product quality assessed was met the quality requirements as regulated by Indonesia National Standard for fish amplang (SNI 7762:2013).